Rationality and the analysis of international conflict - Nicholson, Michael 1933- (Cambridge studies in international relations, 1992)
In this book, Professor Nicholson outlines social scientific approaches to international relations and then describes the problems of rational decision-making in conflict situations. He shows how rationality is in many strategic situations hard to define and often leads to paradoxes such as the prisoners' dilemma. In the following part the author explores rational beliefs about the international system. He examines theories of arms races, alliances and the international problems of ecology. Here he is critical of the classical school of international relations for a lack of rigour in dealing with the problems of evidence and belief. Finally, Michael Nicholson discusses the philosophy of science, policy and ethics. This book is both an exposition and a defence of a social scientific approach to international relations. With its emphasis on social scientific approaches, theory building and testing - and above all its clarity and accessibility - it provides students with a key to understanding the complex field of conflict analysis